Lives of the most eminent literary and scientific men of France, Vol. 2 (of 2) - Shelley, Mary Wollstonecraft, 1797-1851; Lardner, Dionysius, 1793-1859 (Salt Lake City, UT : Project Gutenberg, 2021)
"Lives of the Most Eminent Literary and Scientific Men of France, Vol. 2 (of 2)" is part of a biographical encyclopedia published between 1838-39. Written primarily by Mary Shelley, this volume profiles influential French writers and thinkers from the 14th to 18th centuries. Shelley portrays women sympathetically, examining their social restrictions while arguing for educational opportunities. Her work demonstrates extensive historical knowledge and emerging feminist perspectives, combining research, memoir, and personal commentary to create compelling biographical narratives that reached more readers than her novels. (This is an automatically generated summary.)
Voltaire -- Rousseau -- Condorcet -- Mirabeau -- Madame Roland -- Madame de Staël.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lives_of_the_Most_Eminent_Literary_and_Scientific_Men
Release date is 2021-05-17
Laura Natal Rodrigues at Free Literature (Images generously made available by The Internet Archive.)
Keywords: Authors, French -- Biography